Contested Cornerstones of Nonviolent National Self-Perception in Costa Rica: A Historical Approach - Sebastian Huhn (German Institute of Global and Area Studies (GIGA), 2009)
Crime, violence, and insecurity are perceived as society's biggest problems in contemporary Costa Rica. This degree of priority is especially remarkable because the country has always been considered the peaceful exception in the violent Central American region. In this paper I analyze four cornerstones of the nonviolent national self-perception in the 1940s and 1980s as the fundamental basis for the current talk of crime: the civil war, the abolition of the military, the proclamation of neutrality, and the peace plan for Central America and the subsequent granting of the Nobel Peace Prize. The result of the analysis is the determination that these historical cornerstones were not publicly discussed as expressions of the nonviolent identity for which they are today cited as evidence. – – Gewalt und Kriminalität werden in der costaricanischen Öffentlichkeit heute als die größte gesellschaftliche Bedrohung wahrgenommen. Diese Prioritätensetzung ist nicht zuletzt deshalb bemerkenswert, weil Costa Rica seit langem als die friedvolle Ausnahme in der gewalttätigen zentralamerikanischen Region gilt. Dieser Beitrag untersucht vier Säulen der gewaltlosen Selbstwahrnehmung in den 1940er und 1980er Jahren: den Bürgerkrieg, die Abschaffung des Militärs, die Neutralitätserklärung und den Friedensplan für Zentralamerika, für den Oscar Arias mit dem Friedensnobelpreis ausgezeichnet wurde. Der Beitrag zeigt, dass diese historischen Momente in den 1940er und 1980er Jahren öffentlich nicht unter dem Gesichtspunkt von Gewaltlosigkeit debattiert und wahrgenommen wurden und dass sich die damaligen Debatten nicht mit ihrer heutigen Interpretation als Belege einer gewaltlosen nationalen Identität decken.
Keywords: 300; Costa Rica; violence; crime; social order; national identity; public discourse